3D interactive courseware for education: anatomy of human brain - Muhammad Fathurrahman, Rizal (2015)
3D Interactive courseware for education (Anatomy of Human Brain) is an educational courseware that will provide information about human brain structures, the functions and the interaction towards senses. This could help the user to gain knowledge on human brain related topics and help them to seek information. Plus, there are problems that have been discovered that is lead to this courseware creation which is most of the people is still using traditional methods of seeking information, difficulties to explore the brain directly, the human brain has too many parts to remember and understand, and the waste of paper. The objectives of this project are to study about the human brain, to develop interactive courseware that includes 3D models, and to test the effectiveness and functionality of this courseware. Besides, the methodology that will be used is ADDIE model. The courseware could provide an accurate look at the anatomy of the most important organ in human body. 3D interactive courseware for education would be an outstanding experience of learning for users. Quiz also included in this courseware for users to attempt and evaluate their understanding on human brain.